Unobserved components model(s): Output gaps and financial cycles - Justine Guillochon; Julien Le Roux (European Central Bank (ECB), 2023)
The Global Financial Crisis established that policymakers should consider the stage of the financial cycle to better evaluate the cyclical position of the economy when designing monetary policy decisions. If financial variables are omitted from the estimations of the output gap, a common and unobserved indicator of the business cycle, important financial or external imbalances that may lead to future recessions may not be captured. This paper presents a suite of estimates of output gaps incorporating financial variables. The estimates are based both on small unobserved components models and a large unobserved components model that follows a production function approach. The results show that exploiting the information content of financial variables, which co-move strongly with the output cycle, can sometimes improve output gap estimates. However, these improvements are of a limited magnitude and very sensitive to the choice of the chosen financial variables.
Keywords: C32; E32; E44; E47; E52; 330; Output gap; potential output; financial cycle; monetary policy; unobserved components model